Study of properties of explanted implant with view to reuse - Sethi Kailash; Golwala Paresh (Journal of Integrated Health Sciences)
Introduction: Increasing number of implants is in use for treatment of fracture to get better results. Poor people are more prone to fractures but they are unable to afford these implants. On other hand, explants (removed implants) are not allowed to be reused by law. So why not to reuse suitable explants to alleviate the suffering, which will help these poor patients. Method: Implants were explanted from patients with clinical indication after voluntary consent. They were submitted to microbiological (in microbiology lab), mechanical and metallurgical (by Brinell hardness Machine and under Scanning Electronic Microscope) tests before and after minor modifications in vitro. Results: The properties of explants after minor modifications were compared with properties of new implants and were found to be same. Conclusion: As results are excellent in vitro, now it is high time to test the efficacy of explants in vivo so they can be reused in future patients if found good. This will help economically deprived patients and their families to a great deal. This will also reduce Bio Medical Waste (BMW). This research project is funded by Sumandeep Vidyapeeth, Piparia, Vadodara.